The Cost‐Effectiveness of Screening in the Community to Reduce Osteoporotic Fractures in Older Women in the UK: Economic Evaluation of the SCOOP Study. (22nd February 2018) - Turner, David A; Khioe, Rebekah Fong Soe; Shepstone, Lee; Lenaghan, Elizabeth; Cooper, Cyrus; Gittoes, Neil; Harvey, Nicholas C; Holland, Richard; Howe, Amanda; McCloskey, Eugene; O'Neill, Terence W; Torgerson, David; et al.
ABSTRACT: The SCOOP study was a two‐arm randomized controlled trial conducted in the UK in 12, 483 eligible women aged 70 to 85 years. It compared a screening program using the FRAX® risk assessment tool in addition to bone mineral density (BMD) measures versus usual management. The SCOOP study found a reduction in the incidence of hip fractures in the screening arm, but there was no evidence of a reduction in the incidence of all osteoporosis‐related fractures. To make decisions about whether to implement any screening program, we should also consider whether the program is likely to be a good use of health care resources, ie, is it cost‐effective? The cost per gained quality adjusted life year of screening for fracture risk has not previously been demonstrated in an economic evaluation alongside a clinical trial. We conducted a "within trial" economic analysis alongside the SCOOP study from the perspective of a national health payer, the UK National Health Service (NHS). The main outcome measure in the economic analysis was the cost per quality adjusted life year (QALY) gained over a 5‐year time period. We also estimated cost per osteoporosis‐related fracture prevented and the cost per hip fracture prevented. The screening arm had an average incremental QALY gain of 0.0237 (95% confidence interval –0.0034 to 0.0508) for the 5‐year follow‐up. The incremental cost per QALY gained was £2772 compared with the control arm. Cost‐effectiveness acceptability curves indicated a 93% probability of the intervention being cost‐effective at values of a QALY greater than £20, 000. The intervention arm prevented fractures at a cost of £4478 and £7694 per fracture for osteoporosis‐related and hip fractures, respectively. The current study demonstrates that a systematic, community‐based screening program of fracture risk in older women in the UK represents a highly cost‐effective intervention. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.